Community Preparedness for Health Disasters: A Community Health Literacy Study - Suwarningsih, Suwarningsih (Oshada, 2025)
Increasingly complex health disasters demand community preparedness that relies not only on the formal health care system but also on the community's capacity to understand and respond to health risks. Community health literacy is seen as a strategic element that shapes community preparedness through the collective ability to access, interpret, and use health information meaningfully. This study aims to analyze the role of community health literacy in building community preparedness for health disasters, as well as examining the social, cultural, and information access factors that influence it. The study used a qualitative approach with a literature review method, analyzing various scientific sources in the form of journal articles, academic books, and relevant policy documents. The analysis was conducted thematically to identify patterns, key concepts, and implications of health literacy for health disaster preparedness. The study results indicate that community health literacy serves as a cognitive and social foundation that strengthens preventive behavior, information management capabilities, and collective community responses. Social, cultural factors, and unequal access to information shape variations in health literacy that directly impact the level of community preparedness. This study emphasizes the importance of integrating community health literacy into health disaster preparedness strategies and policies to build adaptive and sustainable community resilience.